A Cost Model for Additive Manufacturing in Construction. Issue 9 (1st November 2022) - Re, Daniele; Biccari, Carla Di; Corallo, Angelo
Abstract: The construction industry faces several challenges every day, which are pushing this sector to start a process of innovation. In this contest, Additive Manufacturing (AM) represents an innovation and digitalization opportunity; on this basis, this work will focus on an assessment of AM as an enabling technology for this industry, especially from a cost perspective. In particular, since there is not yet a suitable cost model for AM in construction, a cost model will be developed to assess whether it is cost effective to use 3D printing in the building industry. The results obtained from the application of the cost model on a case study are very promising as they open up new avenues for considering 3D printing as a valid alternative to traditional construction methods.